Nosečnost po 35. letu - tveganje ali normalen pojav sodobne družbe - Burnik, Mojca (Obzornik zdravstvene nege, 2010)
Introduction: Pregnancy after age 35 has long been connected with heightened risks for both mother and child. However, laterin-life pregnancy is nowadays becoming more widely accepted due to certain social advantages. The aim of this paper is to delineate the scientifically based health risks and argumentsopposing advanced maternal age, and the social benefits of later-in-life motherhood. Methods: Review of 22 relevant sources was performedas gathered by online databases (CINAHL, ProQuest, PubMed, The Cochrane Library and ScienceDirect). Discussion and concIusions: The information summarized through literature research indicates that pregnancy and maternity after 35 years of age have become quite a common phenomenon in contemporary society. Women wish to secure financial stability and adequate housing before starting a family. Prirniparous women 35 years of age or older are of ten well educated and cognisant of a healthy life-style. They search for new information on their own initiative and are psychologically prepared for parenthood with a positive self-esteem. However, they of ten face several health risks associated with late pregnancy, such as high blood press ure or gestational diabetes. There is a higher incidence of chromosome abnormalities in the foe tus as well as premature and low birth weight infants. Studies of ten report of difficult deliveries in this group ofwomen resulting in a highernumber of caesarean sections. Despite certain advantages, getting pregnant later in life also entails some risks that cannot be prevented even by improved medical knowledge and sophisticated technology. As the number of pregnancies over 35 mounts, the risk of pathological pregnancies and deliveries is also on the rise. Along with the above, the literature also questions the moral aspects of1ater-in-life motherhood over forty or even fifty years of age.
Keywords: Databases, Bibliographic; Dejavniki tveganja; human pregnancy; Maternal Age 35 And Over; Nosečnica, starost 35 in več; Nosečnost; Nosečnost, komplikacije; Pregnancy; Pregnancy Complications; Risk Factors; Socioeconomic Factors; Socioekonomski faktorji; starost; Zbirke podatkov bibliografske